Ensiklopedi lintas agama - Roham, Abujamin, 1929- ([Jakarta] : Kerjasama Emerald [dan] PT Intermasa, 2008)
Encyclopedia of religion in Indonesia.
Includes bibliographical references (p. 782-799) and index.
Keywords: Indonesia -- Religion -- Encyclopedias